Analisis Upaya Guru Pendidikan Pancasila Dalam Mencegah Tindakan Bullying Melalui Penguatan Karakter Toleransi Di Era Society 5.0 - Ditania Febrianti; Dadang Mulyana; Cahyono . (CV. ITTC INDONESIA, 2026)
Bullying in the school environment remains a serious problem, especially verbal bullying such as mocking, insulting, and social exclusion among students. Technological developments in the society 5.0 era also influence students’ social behavior, therefore strengthening tolerance character through Pancasila Education is necessary. This study aims to analyze the efforts of Pancasila Education teachers in preventing bullying through strengthening tolerance character at SMK Pekerjaan Umum Negeri Bandung. This study used a qualitative approach with a descriptive method. Data collection techniques were carried out through observation, interviews, and documentation involving teachers and students as research subjects. The results showed that Pancasila Education teachers play an important role in preventing bullying through instilling tolerance values, habituating mutual respect, providing role models, and supervising students’ behavior both at school and on social media. Teachers also collaborate with counseling teachers and school authorities in creating a safe and inclusive learning environment so that verbal bullying gradually decreases. Strengthening tolerance character through Pancasila Education is an effective effort in shaping students who are moral and respectful of differences in the society 5.0 era..